LOGISTIC APPROACH TO AUTOMOTIVE TRANSPORT ENTERPRISE MANAGEMENT - T. R. Kisel; L. A. Bujko (Наука и техника)
The paper proposes a general planning algorithm concerning transportation activity on the basis of logistic principles that reveals interdependence and interrelation of such problems as transportation route, determination of the shortest distances, selection of rolling stock and utilization of transport means.